Kesalahan Penerapan Afiksasi pada Teks Eksposisi Siswa Kelas X Semester Ganjil SMA Negeri 13 Bandar Lampung - Uswatun Hasanah; Untung Nopriansyah (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
The aim of the research is to find out and describe errors in the form of affixation in the exposition texts of class The affixations analyzed include prefixes, suffixes and combinations of prefixes and suffixes. The basis for raising this problem was because exposition texts written by students still found errors in the application of affixation.The research method uses descriptive qualitative. The research will be conducted at SMA Negeri 13 Bandar Lampung for the 2020/2021 academic year. Data collection uses assignment techniques or expository text writing tests. The results of the students' exposition texts were then analyzed based on qualitative affixation errors.The results of the research show that in the exposition texts of class Prefix errors in exposition text are the most common and frequently encountered errors. Errors occur because students have a wrong understanding of 'di-' as a prefix and di' as a preposition. Suffix errors in students' exposition texts were found but not as many as prefix errors. Mistakes occur because students are not careful in using the ending 'nya' in sentences, causing confusion in the meaning of the sentence. Confix errors in the exposition texts of class X students were found in the forms 'di-kan' and 'di-i'. A fatal mistake for students is using this confix because it separates 'di' from the endings 'kan' and 'i'.